Factors Associated with Anxiety and Depression among Diabetes, Hypertension, and Heart Failure Patients at Dessie Referral Hospital, Northeast Ethiopia. (16th May 2020) - Edmealem, Afework; Olis, Caridad Sanchez
Abstract : Background . Anxiety and depression are common in patients with diabetes, hypertension, and heart failure. However, they are usually unrecognized and untreated especially in developing countries. Identifying factors associated with anxiety and depression is helpful for early screening and management. Objective . This study is aimed at assessing factors associated with anxiety and depression among diabetes, hypertension, and heart failure patients at Dessie Referral Hospital, Northeast Ethiopia. Methods . An institutional-based cross-sectional study was conducted in Dessie Referral Hospital from February 22, 2019 to April 6, 2019. A total of 404 diabetic, hypertension, and heart failure patients were included through systematic sampling technique. The data were collected by face-to-face interview. After data collection, the data were cleaned and presented with text, graphs, and tables. Multivariable binary logistic regression was deployed to identify factors at a P value of < 0.05. Result . A total of 384 patients participated with a 94.8% response rate. Among these, 32% and 5.73% of them had anxiety and depression, respectively. Patients who did not read and write develop anxiety 7.89 times more likely compared with those whose educational status is diploma and above (AOR: 7.89; 95% CI: 3.08-20.26; P = 0.001 ). Patients who took substances like chat, cigarette, shisha, hashish, and alcohol develop anxiety 2.56 times more likely compared with their counterparts (AOR: 2.56; 95% CI: 1.05–6.23; P = 0.038 ). Patients whose level of physical activity is inactive develop depression 24 times more likely than patients who did a health-enhancing physical activity. Patients who are widowed develop depression 5 times more likely compared with married patients. Conclusion and Recommendations . Low educational level, being single and widowed, substance use, poor perception towards prognosis of illness, and monthly income were factors associated with anxiety. On the other hand, being single and unable to do physical activity were statistically associated with depression. Patients with low educational level and monthly income should be screened and supported for anxiety. Health care providers should provide advice to patients about the importance of physical activity to prevent depression.